Orchid Mycorrhizal Fungi: Identification of Rhizoctonia from West Kalimantan - ROSA SURYANTINI; REINE SUCI WULANDARI; RINA SRI KASIAMDARI (Microbiology Indonesia, 2015)
Orchid is an ornamental plants with high economic value. The excessive exploitation of orchids threatened or even endangered the species, especially those of the epiphytic orchids (Appendiculla sp., Calanthe vestita, and Bulbophyllum beccarii) in West Kalimantan. The discovery of the interaction between orchids and mycorrhizal fungi raises the possibility of ex situ conservation of orchids and it will ensure the success of orchid conservation. Orchid mycorrhizal fungi belongs to the group of Rhizoctonia-like,in which comprised of different genus such as Ephulorhiza, Ceratoriza, and Tullasnela. So far, there is no report on the identit of orchid mycorrhiza associated with the epiphytic orchids in West Kalimantan. The purpose of this study was to identify Rhizoctonia-like associated with Appendiculata sp., Calanthe vestita, and Bulbophyllum beccarii roots in the forest of Raya Pasi and Gunung Bawang, West Kalimantan. The methods were isolation and identification of Rhizoctonia-like from healthy orchid's root based on their morphological characteristics (such as the colony colour, hyphal cell size, sclerotial, concentric circles and monilioid cell, number of nuclei per cell), observation of peloton in root tissue and grouping of isolates. Based on identification of orchid mycorrhiza on the roots of the three species of orchids from West Kalimantan, it was observed that Ceratorhiza sp. was associated with Appendiculla sp.,Ephuloriza sp. with C. vestita, and Tullasnela sp. with B. beccarii roots, respectively. This result is preliminary information and it is still need to be further studied, especially on the role of Rhizoctonia-liker as orchid mycorrhizal fungi in association with the epiphytic orchid for conservation.Â